Preliminary investigations of anti-cancer properties of Myrmecodia Pendens on human oral cancer HSC-3 cell lines - Irfanita, Nining; Eddie, Shah; Aziz, N.A.; Ichwan, Solachuddin J. A.; Lestari, Widya (Elsevier, 2019)
Myrmecodia pendens (M. pendens) or also known as Sarang semut is an epiphytic plant which might have potential as a new source of alternative therapeutic agent. Recently, it is reported that M. pendens can inhibit the proliferation of HeLa and MCM- B2 cell lines. We report here for the first time the anti-cancer potential of M. pendens on oral cancer cells derived from human oral cavity, HSC-3 cell lines. MTT assay results showed that M. pendens crude extract markedly induced cytotoxicity on HSC-3 cell lines after 24 h (IC50 = 5 mg/mL) and 48 h (IC50 = 3 mg/ml). The apoptotic activity induced by M. pendens was detected in HSC-3 cell lines by flow cytometry within 24 h. These results suggest that M. pendens may be a potential candidate for oral cancer treatment